Assessment of Pre-Service Chemistry Teachers’ Laboratory Teaching Self-Efficacy and Lesson Plan Quality for Deep Learning Readiness - Setia Rahmawan; Dea Santika Rahayu; Muhammad Zamhari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Laboratory-based instruction is fundamental in chemistry education because it supports conceptual understanding through direct engagement with phenomena, evidence generation, and scientific reasoning. At the same time, current curriculum reforms in Indonesia emphasise deep learning readiness, requiring learning designs that promote inquiry, higher-order thinking, and meaningful technology use. This study examines the alignment between pre-service chemistry teachers' laboratory-teaching self-efficacy and the quality of their laboratory-oriented lesson plans in fostering deep learning readiness. Using a quantitative descriptive design complemented by systematic document analysis, the study involved 46 pre-service chemistry teachers enrolled in a school-based practicum course at an Indonesian university. Data were collected using (1) an adapted Chemistry Laboratory Teaching Self-Efficacy Scale covering experimental processes, technology use, and laboratory safety and (2) an analytic rubric to evaluate lesson plans across deep learning orientation, inquiry and reasoning structure, practicum design, higher-order assessment alignment, technology integration, safety/risk documentation, and instructional clarity. Descriptive statistics summarised efficacy and lesson plan quality, while cross-tabulation explored patterns between perceived capability and planning competence. Findings indicate that most participants reported high to very high laboratory-teaching self-efficacy, particularly in experimental procedures and safety. However, most lesson plans were rated moderate, with recurring weaknesses in the design of open inquiry, explicit higher-order assessment tasks, the purposeful integration of digital tools, and detailed safety documentation. The results suggest a partial misalignment between strong self-beliefs and the demonstrated quality of deep-learning-oriented lesson planning. The study highlights the need for teacher education programmes to combine explicit rubric-based lesson planning instruction, iterative feedback cycles, and technology-rich laboratory pedagogy to strengthen deep learning readiness in chemistry education. Keywords: Self-efficacy; lesson plan assessment; laboratory-based learning; deep learning; chemistry education